EVALUATION OF FORCED AERATED AND TURNED PILE COMPOSTING OF ROSE OIL PROCESSING WASTES - Ekinci, Kamil; Tosun, İsmail; Sülük, Kemal; Sevik, Fevzi; Kumbul, Barbaros Salih; Bitrak, Necati Berk (Technical Univ Wroclaw, 2022)
Composting of rose oil processing solid wastes was experimented by two different aeration methods: forced aeration and mechanical turning. The objective of this study was to assess which aeration methods were the most convenient for the composting process. Assessment of aeration methods was performed based on the parameters such as temperature, O-2, CO2, CH4 concentration profiles, and physical and chemical properties of the finished composts. The two aeration methods were also compared based on the energy consumed by aeration per unit organic matter loss (OML) of composting, which is a major proportion of operating costs. Although composting performance parameters of temperature and O-2/CO2 in the function of time showed some differences, similar end-product quality in terms of moisture, pH, electrical conductivity, NH4+-N and NO3--N and contents was obtained. These results suggested that both methods (forced aeration and mechanical turning) may be utilized for composting operation of rose oil processing solid wastes. However, in this study, energy consumed by aeration provided by mechanical turning per unit OML of composting was 1.24 times higher than that of forced aeration. Furthermore, mechanical turning created anaerobic conditions for the formation of CH4 concentration in the pile, which was higher than that of the forced aeration.
Keywords: Sewage-Sludge; Olive; Quality